Adventitious agents and live viral vectored vaccines: Considerations for archiving samples of biological materials for retrospective analysis. Issue 51 (12th December 2016) - Klug, Bettina; Robertson, James S.; Condit, Richard C.; Seligman, Stephen J.; Laderoute, Marian P.; Sheets, Rebecca; Williamson, Anna-Lise; Gurwith, Marc; Kochhar, Sonali; Chapman, Louisa; Carbery, Baevin; Mac, Lisa M.; et al.
Abstract: Vaccines are one of the most effective public health medicinal products with an excellent safety record. As vaccines are produced using biological materials, there is a need to safeguard against potential contamination with adventitious agents. Adventitious agents could be inadvertently introduced into a vaccine through starting materials used for production. Therefore, extensive testing has been recommended at specific stages of vaccine manufacture to demonstrate the absence of adventitious agents. Additionally, the incorporation of viral clearance steps in the manufacturing process can aid in reducing the risk of adventitious agent contamination. However, for live viral vaccines, aside from possible purification of the virus or vector, extensive adventitious agent clearance may not be feasible. In the event that an adventitious agent is detected in a vaccine, it is important to determine its origin, evaluate its potential for human infection and pathology, and discern which batches of vaccine may have been affected in order to take risk mitigation action. To achieve this, it is necessary to have archived samples of the vaccine and ancillary components, ideally from developmental through to current batches, as well as samples of the biological materials used in the manufacture of the vaccine, since these are the most likely sources of an adventitious agent. The need for formal guidance on such vaccine sample archiving has been recognized but not fulfilled. We summarize in this paper several prior major cases of vaccine contamination with adventitious agents and provide points for consideration on sample archiving of live recombinant viral vector vaccines for use in humans.